Marine Clay Stabilisation Using An Encased Stone Column With Tyre Chips As Aggregates - Naga Sivaji; Rangaswamy. K (Deep Foundations Institute, 2022)
A stone column is one of the most commonly employed methods of ground improvement techniques. This method used to increase the strength, decrease the compressibility of loose granular and finegrained soils. Also, it accelerates the consolidation in clays and reduces the liquefaction potential of sands and silt soils. In general, the stone column contains 15 to 75mm stone aggregates. In reality, it is not easy to avail the natural stone aggregates due to unavailability in locally nearby places. Present work aims to replace the stones partially or entirely by scrap tyre chips as an alternative material. The utilisation of recycled tyre chips in ground improvement is an environmentally friendly solution and avoid the disposal of tyre chip waste in large pits. Model tests conducted on marine clay with encased end bearing stone columns (ESC) constructed with a mixture of stone aggregate and tyre chips with sizes 4.75 to 10mm. The column diameter is 75 mm, L/d ratio maintained to 5.3. Non-woven geotextile wrapped encased stone column has introduced in the soft marine clay model. Encasement prevents the lateral squeezing of aggregates into the surrounding clay and protects the drainage function of the stone column. A set of load-settlement tests were conducted on both the clay model and clay model treated with the stones-tyre chips column. The model was loaded by the tri-axial loading frame. Shear strength parameters of stones and tyre chips were determined by large size direct shear tests. Model test results are concluding that the load-carrying capacity of the clay is improved significantly after installing the stone column in it. The encasement increases the load-carrying capacity and stiffness of the ordinary stone column. It is also proved that the stone aggregate could be replaced partially by tyre chips up to 60% without a significant reduction in its performance.